Prevalence, determinants, and effects of violence during pregnancy: A maternity-based cross-sectional study in Luanda, Angola - Tazi Nimi; Silvia Fraga; Diogo Costa; Paulo Campos; Henrique Barros (AOSIS, 2020)
Information on the extent of violence against women is scarce in Angola. This study aims to estimate the prevalence of violence against pregnant women in Angola and to identify its sociodemographic determinants and effects on pregnancy outcomes. A cross-sectional study was conducted between December 2012 and February 2013, involving 995 women who delivered at a Maternity in Luanda, Angola. Information was collected through questionnaires administered by interviewers. The prevalence of violence during pregnancy was 13.0%. Exclusively physical, psychological or sexual violence was reported by 4.3%, 7.7% and 0.2% of the women, respectively. After adjustment, the occurrence of physical violence decreased with increasing age and education, and was more common among women who consumed alcohol during pregnancy, while psychological violence was significantly more frequent among women aged 20 to 24 years and those who had their first sexual intercourse before the age of 15, and less frequent among those who were married or in cohabitation. This first study describing violence against pregnant Angolan women showed that violence is a frequent event, supporting that violence assessment should be considered in antenatal care.